WHETHER TO PUNISH OR TO FORGET: THE ETERNAL DILEMMA OF TRANSITIONAL JUSTICE? - Krtolica, Marko (Institute for Legal-Economic Research an Education I U R I D I C A P R I M A, 2021)
The development of the concept of transitional justice has been one of the most dramatic events in the legal and political science theory. It is hard to find another concept or theory in legal and political science theory, that has managed to develop at such a pace as the concept of transitional justice. In less than 60 years, the concept of transitional justice has grown from an exception to a rule. However, despite such a dramatic development, the rise of the concept of transitional justice has been followed by a great number of dilemmas. Thus, regarding the concept of transitional justice, it is often emphasized that it is a retroactive justice and that it has the capacity to destabilize fragile post-conflict and post-repressive societies. Additionally, unrealistic expectations for justice, the possibility of misuse for revenge, as well as the need to address other issues (economic, infrastructural, social, etc.) are usually highlighted as dilemmas regarding the implementation of transitional justice. Such dilemmas have marked the development of transitional justice during the XX century, but the intensive application of this concept has brought in theory the statement that the implementation of transitional justice in post-conflict and post-repressive societies contributes to the establishment of a democratic society. A contribution like this is emphasized because the implementation of transitional justice in post-conflict and post-repressive societies contributes to non-repetition of crimes committed in the past, protection of the system from undemocratic forces, building a democratic political culture and positive economic results. In this regard, in theory is generally accepted that transition societies, which choose to ignore the need to face their problematic past, have a problem putting peace, stability, the rule of law and democracy on a solid grounds.
Keywords: politics, political system, democracy, transition, transitional justice